Comparison of whole genome sequencing performance from fish swabs and fin clips - Annabell Macphee; Temitope Opeyemi Oriowo; Nils Sternberg; Madlen Stange (BMC Research Notes)
Abstract Objective Fin clipping is the standard DNA sampling technique for whole genome sequencing (WGS) of small fish. The collection of fin clips requires anaesthesia or even euthanisation of the individual. Swabbing may be a less invasive, non-lethal alternative to fin-clipping. Whether skin and gill swabs are comparable to fin clips in terms of DNA extraction quality and sequence read mapping performance from WGS was tested here on Eurasian minnows (Phoxinus phoxinus). Results Of 49 fin clips, all met the DNA concentration threshold of 20 ng/μl, whereas 43 of 88 swabs met this requirement. Preserving swabs in ATL buffer and treatment with Proteinase K during DNA extraction consistently raised skin swab DNA concentrations above the cut-off. All samples passed the A260/A280 absorbance ratio cut-off of 1.3. Ultimately, 93.88% of the fin clips, 30.61% of the skin, and 7.69% of the gill swabs were suitable for sequencing. Mapping performances of all three tissues were comparable in reads passing quality filtering, percentage of reads mapping to the P. phoxinus reference genome, and coverage. Overall, skin swabs treated with Proteinase K during extraction, can match fin clips in WGS performance and represent a viable non-invasive DNA sampling alternative.